Suppression of joint destruction with subcutaneous tocilizumab for Japanese patients with rheumatoid arthritis in clinical practice. Issue 5 (2nd September 2020) - Nakashima, Yasuharu; Kondo, Masakazu; Shono, Eisuke; Ishinishi, Takashi; Tsukamoto, Hiroshi; Kuroda, Koji; Maeyama, Akira; Harada, Hiroshi; Maekawa, Masayuki; Shimauchi, Takashi; Nagamine, Ryuji; Jojima, Hiroshi; et al.
Abstract: Objectives: To investigate the efficacy of suppressing joint destruction with subcutaneous tocilizumab (TCZ-SC) for Japanese rheumatoid arthritis (RA) patients in the real-world clinical setting. Methods: This 1-year prospective, multicenter study included 110 RA patients in whom TCZ-SC was newly initiated. Primary endpoint was the change from baseline in vdH-modified total Sharp score (mTSS) at week 52. Structural remission was defined as yearly mTSS of 0.5 or less. Disease activity was evaluated using the disease activity score (DAS28-ESR) and clinical disease activity index (CDAI). Results: At baseline, the patients' mean age was 58.6 years, and the mean disease duration was 10.6 years. The proportion of patients who were naïve for biologics was 44.5%, and 64.5% concomitantly received methotrexate. The yearly mTSS showed significant improvement from 9.41 before TCZ-SC initiation to −0.15 after 52 weeks. The structural remission rate was 76.1%. After 52 weeks, the DAS28-ESR and CDAI remission rates were 52% and 21%, respectively. Although the previous usage of biologics and baseline disease activity significantly affected the clinical remission, no factors with significant effects on structural remission were identified. Conclusion: These findings support the efficacy of TCZ-SC in suppressing disease activity as well as joint destruction over a 1-year period.